THE DEVELOPMENT OF INNOVATION AMBIIJJ:: 1'J::RITY MODEL AND ITS INFLUENCE ON THE FIRM PERFORMANCE IN BROILER POULTRY FARMERS IN WEST JAVA - Bagus Profityo, Werda
The developmenl oflhe broiler poulfly induslly has experienced a signlficant increa.1e along wilh lhe increasing public demand.for meal consumplion. However. in 20/ 9, many broiler poult1y farmers are forced lo close down /heir businesses becaw e the price of broilers in living conditions continues to be below I he Production Cost (I IPP). Broiler poulfly farmers experience obstacles which include erratic price jluctuatiom and intense competition. Environmental forces are considered to produce a greal deal of pressure in the business operational processes. Innovation ambidexterity is an innovalion capability that must be owned by broiler poultry farmers in managing exploration and exploitation simultaneously to improve business pe1:(ormonce. Some factors that are considered influential in increasing innovation amhidexterily include technology, organization, and environment. Thus, this study aims to develop a model !hal illustrates the innovation ambidexterity of broiler poullry 10 improve firm performance. This study also analyzes the factors !hat can affect innovmion ambidexterity and the moderating effect of environmental dynamics on firm performance. This research uses quantitative methods. The sampling technique uses non probability sampling with convenience sampling technique. Data collection was carried 0 111 by distributing questionnaires to broiler poultry farmers in West Java. A lola/ of I 23 queslionnaires were used as dala in this study. The analysis technique in thi .H/I(~y uses Partial Least Square- Structural Equation Modeling (PLS- EM) which includes measurement model analysis and structural model analysis. Data processinx wa.) performed using IBM SPSS software to test the validity and reliability of que ·tion items and SmartPLSfor PLS-SEM analysis. The results of this study indicate that innovation ambidexterity htls u dir('ct il!flu nee on firm petformance while the influence of environmemal dynamism 0 11 ./irm performance is partially mediated by innovation ambidexterity. l11is .1·hows thai the infernal organizational struclure in a very dynamic environmenl provide.,· a stimulus for the development of innovation ambition that will u/rimarcfy have a positi\'t' imp(ll'l on firm performance. In addition, the results of the study also showed thtlf technological capability and owner-manager characteristics have a positive t~//t•c:t on innovation ambidexterity and have an indirect effect on .finn pe1:{ormonce.